Menganalisis Sekolah Dasar Sebagai Organisasi Pendidikan Sistem Sosial di SDN 17 Kolono - Abubakar; Atriani; Altin (Digital Pedagogy in Primary Education Journal, 2026)
Elementary schools are educational institutions that function not only as places for knowledge transfer but also as complex social systems. This study aimed to analyze SDN 17 Kolono as an educational organization from a social system perspective. The study employed a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, students, and educational staff. Data were analyzed through data reduction, data presentation, and conclusion drawing, while data validity was tested using source and method triangulation. The findings showed that SDN 17 Kolono has a social structure involving the principal, teachers, students, and educational staff who interact to achieve educational goals. Social interactions within the school environment reflect the values of discipline, responsibility, cooperation, and mutual respect, which support the learning process and students’ character development. Harmonious relationships between the school and the community also create an educational environment conducive to students’ academic, social, and character development. Keywords: educational organization, elementary school, social system